Resin composition, coating composition containing the same, lamination electrode, lamination separator, nonaqueous electrolyte secondary battery and method for producing the same
By using a specific proportion of vinylidene fluoride copolymer, combining softening and chemical interactions, the problem of insufficient dry bonding of the positive electrode and the negative electrode in the prior art is solved, and efficient bonding of the positive electrode and the negative electrode is achieved, which improves the two Performance and safety of secondary batteries.
Patent Information
- Application Number
- CN202180055815.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-07-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-07-14
AI Technical Summary
In the prior art, it is difficult to simultaneously improve the dry bonding of the positive electrode and the negative electrode through a single resin composition, especially the problem of increasing the bonding of the negative electrode and the dry bonding is low.
The resin composition formed by softening and Chemical interaction improves dry bonding between the positive electrode and the negative electrode.
High-dry adhesion to the positive electrode and the negative electrode is achieved, the stability and adhesion of the resin layer are ensured, and the yield and safety of the secondary battery are improved.
Smart Images

Figure FDA0005014917580000011 
Figure GDA0004113286500000071 
Figure GDA0004113286500000191
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a coating composition containing the resin composition, a lamination electrode, a lamination separator, a nonaqueous electrolyte secondary battery and a method for producing the same. Background Art
[0002] In recent years, non-aqueous electrolyte secondary batteries (hereinafter, also referred to as "secondary batteries") are used for various purposes and are required to have higher capacity. In the past, many wound secondary batteries have been developed, which are formed by winding electrodes (in this specification, when there is no need to distinguish between positive and negative electrodes, they are collectively referred to as "electrodes") and separators. However, in recent years, when making secondary batteries with higher capacity,
[0003] A laminated secondary battery in which electrodes and separators are laminated has attracted attention. In addition, since such a secondary battery is used in various applications, more attention has been paid to safety.
[0004] Here, the electrodes and separators of stacked secondary batteries are easily offset compared to wound secondary batteries. For example, when manufacturing a secondary battery, when the stack of electrodes and separators is transported or filled into an outer shell, the electrodes and separators are easily offset from the desired position or wrinkled. In addition, in the case of a wound type, as time passes after winding, the wound electrode / spacer stack becomes loose, and may be offset during transportation or when inserted into the outer shell. Moreover, in a secondary battery using a bag-type outer shell, when a force is applied from the outside during use of the secondary battery, the electrodes,
[0005] The position of the spacer may be shifted. If such position shift or wrinkles occur in a secondary battery, not only the yield rate is affected, but also the desired performance in terms of battery performance and safety is difficult to obtain.
[0006] Therefore, a method of forming a porous adhesive layer on one or both sides of a spacer to bond the electrode and the spacer has been proposed (Patent Document 1). The porous adhesive layer comprises a vinylidene fluoride copolymer having a structural unit derived from vinylidene fluoride, a structural unit derived from hexafluoropropylene, and a structural unit derived from a carboxyl group-containing monomer.
[0007] In order to improve the adhesion between the separator and the electrode, it has been proposed to form a layer by coating a composition containing a vinylidene fluoride copolymer containing a structural unit derived from vinylidene fluoride and a structural unit derived from a specific carboxyl group-containing monomer on the separator (Patent Document 2).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2017-117788
[0011] Patent Document 2: International Publication No. 2014 / 002937 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] Here, there are cases where an adhesive layer is formed on the surface of the spacer as in the above-mentioned Patent Document 1 and Patent Document 2, a case where the adhesive layer is bonded to the electrode before the electrolyte is injected (hereinafter also referred to as "dry bonding"), and a case where the adhesive layer is bonded to the electrode after the electrolyte is injected (hereinafter also referred to as "wet bonding"). In addition, during bonding before the electrolyte is injected (dry bonding), the resin in the resin-containing layer softens and penetrates into the electrode layer to bond the spacer and the electrode. On the other hand, during wet bonding, the resin swollen by the electrolyte melts during hot pressing, penetrates into the electrode layer, and gels by cooling. As a result, the resin is in close contact with the spacer and the electrode, and the spacer and the electrode are bonded. That is, in dry bonding and wet bonding, the bonding mechanism is different, and a resin with good wet bonding is generally different from a resin with good dry bonding. Furthermore, in the above-mentioned Patent Documents 1 and 2, resin compositions with good wet adhesiveness are proposed, but resin compositions with good dry adhesiveness have not been studied. Furthermore, the adhesive layers described in the above-mentioned Patent Documents 1 and 2 have the problem of low dry adhesiveness.
[0014] In addition, in the prior art, it is difficult to improve the dry adhesion to both the positive and negative electrodes by only a single polyvinylidene fluoride copolymer. As described above, during dry bonding, the resin in the bonding layer softens, and the resin is closely attached to the spacer and the electrode, thereby bonding the spacer and the electrode. However, due to the different physical structures of the electrode surfaces of the positive and negative electrodes and the different types of adhesives used in each electrode, it is difficult to obtain high dry adhesion to both the positive and negative electrodes by a single resin.
[0015] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a resin composition having excellent dry adhesiveness to both positive and negative electrodes.
[0016] Technical Solution
[0017] The present invention provides the following resin composition (coating agent).
[0018] A resin composition comprising a vinylidene fluoride copolymer having: 73.7% by mass or more and 96.9% by mass or less of structural units derived from vinylidene fluoride, 0.1% by mass or more and 1.3% by mass or less of structural units containing a carboxyl group, and 3% by mass or more and 25% by mass or less of other structural units that do not contain a carboxyl group and are derived from a compound copolymerizable with the vinylidene fluoride (wherein the total amount of structural units constituting the vinylidene fluoride copolymer is set to 100% by mass), wherein the intrinsic viscosity of a solution obtained by dissolving 4 g of the vinylidene fluoride copolymer in 1 L of N,N-dimethylformamide at 30° C. is 0.5 dL / g or more and 3 dL / g or less.
[0019] The present invention also provides the following coating composition (coating liquid).
[0020] A coating composition comprises the above resin composition and a solvent.
[0021] The present invention also provides the following lamination electrode.
[0022] A stacking electrode comprises: an electrode; and a resin-containing layer disposed on at least one surface of the electrode, the layer comprising the above-mentioned resin composition.
[0023] The present invention also provides the following lamination spacer.
[0024] A lamination spacer comprises: a spacer and a resin-containing layer disposed on at least one surface of the spacer, and comprising the above-mentioned resin composition.
[0025] The present invention also provides the following nonaqueous electrolyte secondary battery.
[0026] A nonaqueous electrolyte secondary battery comprises a positive electrode, a separator and a negative electrode, and further comprises a resin-containing layer comprising the above-mentioned resin composition between the positive electrode and the separator and / or between the negative electrode and the separator.
[0027] The present invention also provides the following method for producing a nonaqueous electrolyte secondary battery.
[0028] A method for manufacturing a non-aqueous electrolyte secondary battery, the manufacturing method comprising: a step of applying the above-mentioned coating composition on at least one side of at least one member selected from the group consisting of a positive electrode, a separator, and a negative electrode, and curing it to form a resin-containing layer; a step of stacking the positive electrode, the separator, and the negative electrode in a manner such that the resin-containing layer is located between the positive electrode and the separator, and / or between the negative electrode and the separator to form a stack; and a step of hot pressing the stack.
[0029] Beneficial Effects
[0030] The resin composition of the present invention is excellent in dry adhesion to both positive electrodes and negative electrodes. DETAILED DESCRIPTION
[0031] 1. Resin composition (coating agent)
[0032] The resin composition (coating agent) of the present invention is a resin composition mainly used to form a resin-containing layer for fixing an electrode and a separator of a non-aqueous electrolyte secondary battery. However, the use of the resin composition (coating agent) is not limited to the resin-containing layer. In this specification, the terms "resin composition" and "coating agent" are used with the same meaning.
[0033] As described above, in the known resin composition containing a vinylidene fluoride copolymer, it is difficult to simultaneously improve the dry adhesiveness to the positive electrode and the dry adhesiveness to the negative electrode, and it is particularly difficult to improve the adhesiveness to the negative electrode.
[0034] In response to such problems, the present inventors conducted in-depth research and found that by configuring a resin composition (resin-containing layer) comprising the following vinylidene fluoride copolymer between the separator and the electrode, good dry adhesion to both the positive and negative electrodes can be achieved. The vinylidene fluoride copolymer comprises, in a specified ratio, structural units derived from vinylidene fluoride, structural units containing carboxyl groups, and other structural units in addition thereto, and has an inherent viscosity of greater than 0.5 dL / g and less than 3 dL / g.
[0035] The reasons can be considered as follows. As mentioned above, during dry bonding, the vinylidene fluoride copolymer in the resin-containing layer needs to be fully softened and fully adhered to the electrodes, separators, etc. However, in the positive electrode and the negative electrode, the physical structure and chemical structure of the surface are mostly different. Specifically, the shapes of the active materials in the positive electrode and the negative electrode are different, and of course, the smoothness of the electrode surface is different. This smoothness greatly affects the physical adhesion. On the other hand, in the positive electrode and the negative electrode, the adhesives used are mostly different. For example, sometimes the positive electrode adhesive is vinylidene fluoride, and the negative electrode adhesive is styrene-butadiene rubber / carboxymethyl cellulose, and their chemical properties are very different. In this way, in order to achieve effective adhesion on both sides of the two surfaces with different physical and chemical structures, it is necessary to control the mechanical properties of the resin, introduce functional groups, and perform chemical modification.
[0036] Therefore, the vinylidene fluoride copolymer contained in the resin composition of the present invention contains a certain amount of structural units derived from vinylidene fluoride and other structural units other than the structural units containing carboxyl groups. Therefore, the vinylidene fluoride copolymer has appropriate flexibility when softened, and is fully in close contact with electrodes and spacers. In addition, at this time, the carboxyl group in the vinylidene fluoride copolymer interacts chemically with the OH group on the surface of the spacer and the electrode. In this way, the vinylidene fluoride copolymer contained in the resin composition of the present invention has both the softening of the vinylidene fluoride copolymer; and the different close-fitting mechanisms of the chemical interaction between the carboxyl group and the electrode, spacer, etc. Therefore, in the physical close contact achieved by softening, for the electrode surface with insufficient close contact force, the close contact force is supplemented by the chemical interaction between the carboxyl group and the electrode, spacer, etc. On the other hand, in the chemical interaction between the carboxyl group and the electrode, spacer, etc., for the insufficient electrode surface, the close contact force is supplemented by the physical close contact achieved by softening. Therefore, the resin composition of the present invention has excellent dry adhesion to both the positive and negative electrodes.
[0037] Moreover, the intrinsic viscosity of vinylidene fluoride copolymer is, for example, a physical property representing the molecular weight of vinylidene fluoride copolymer, and if the intrinsic viscosity is too high, then, for example, during dry bonding, vinylidene fluoride copolymer is not easy to fit closely with electrode and spacer surface. In addition, if the intrinsic viscosity is too low, the stability of the resin composition and coating composition comprising vinylidene fluoride copolymer is reduced, and it is not easy to form a layer containing resin. To this, in the present invention, the intrinsic viscosity of the above-mentioned vinylidene fluoride copolymer is in a certain range, so the stability of the resin composition and coating composition comprising the vinylidene fluoride copolymer is good, and dry bonding becomes good.
[0038] It should be noted that the resin composition of the present invention may also include components other than the vinylidene fluoride copolymer within the scope of not damaging the purpose and effect of the present invention. As components other than the vinylidene fluoride copolymer, dispersants, defoamers, wetting agents, etc. may be listed. Wherein, the amount of the vinylidene fluoride copolymer in the resin composition is preferably more than 90% by mass, more preferably more than 95% by mass. Below, the vinylidene fluoride copolymer is described.
[0039] (vinylidene fluoride copolymer)
[0040] The resin composition of the present invention may contain the following vinylidene fluoride copolymers. The resin composition may contain one or more vinylidene fluoride copolymers, or may contain two or more vinylidene fluoride copolymers.
[0041] The amount of structural units derived from vinylidene fluoride contained in the vinylidene fluoride copolymer is 73.7% by mass or more and 96.9% by mass or less, preferably 78% by mass or more and 95% by mass or less, and more preferably 83% by mass or more and 93% by mass or less, when the total amount of structural units of the vinylidene fluoride copolymer is set to 100% by mass. As described above, if the amount of structural units derived from vinylidene fluoride is 73.7% by mass or more, the vinylidene fluoride copolymer has appropriate crystallinity and it is easy to properly maintain the strength of the resin-containing layer. On the other hand, if the amount of structural units derived from vinylidene fluoride is 96.9% by mass or less, the amount of structural units containing carboxyl groups and the amount of other structural units become relatively sufficient, and the dry adhesion is easily improved due to the interaction of carboxyl groups. The resin-containing layer is easily softened by heating, and the dry adhesion is easily improved. The above-mentioned amount of structural units derived from vinylidene fluoride can be obtained by using 19 The determination was made by analyzing the vinylidene fluoride copolymer using F-NMR.
[0042] The amount of the carboxyl-containing structural unit included in the vinylidene fluoride copolymer is 0.1% by mass or more and 1.3% by mass or less when the total amount of the structural unit of the vinylidene fluoride copolymer is set to 100% by mass, preferably 0.2% by mass or more and 1.0% by mass or less, more preferably 0.3% by mass or more and 1.0% by mass or less. If the ratio of the carboxyl-containing structural unit is more than 0.1% by mass, the carboxyl group is easily interacted with the functional group in the electrode and the spacer, or the carboxyl group is easily interacted with, and the dry adhesion of the resin-containing layer of the resin composition is improved. On the other hand, if the amount of the carboxyl-containing structural unit is less than 1.3% by mass, the stability of the resin composition, the coating composition, etc. is easily improved. The amount of the carboxyl-containing structural unit in the vinylidene fluoride copolymer can be determined, for example, by the known method disclosed in Japanese Patent Publication No. 2015-172101.
[0043] Here, the above-mentioned carboxyl-containing structural unit is a structural unit obtained by a compound containing a carboxyl group. The type of the compound containing a carboxyl group is not particularly limited, for example, preferably a compound containing a carboxyl group and an unsaturated double bond, etc. Examples of such compounds include: unsaturated dibasic acid, unsaturated dibasic acid monoester or a compound shown in the general formula (1) described later. The vinylidene fluoride copolymer may contain only one structural unit derived from them, or may contain two or more structural units derived from them.
[0044] Examples of the unsaturated dibasic acid include compounds containing an unsaturated double bond and two carboxyl groups or anhydride groups. The number of carbon atoms of the unsaturated dibasic acid is preferably 5 to 8. Specific examples thereof include fumaric acid, maleic acid (anhydride), citraconic acid, and phthalic acid. It should be noted that the "carboxyl group" in this specification also includes anhydride.
[0045] Examples of unsaturated dibasic acid monoesters include compounds having an unsaturated double bond, a carboxylic acid, a carboxylic acid ester, etc. The number of carbon atoms of the unsaturated dibasic acid monoester is preferably 5 to 8. Specific examples of unsaturated dibasic acid monoesters include monomethyl fumarate, monoethyl fumarate, monomethyl maleate, monoethyl maleate, monomethyl citrate, monoethyl citrate, monomethyl phthalate, and monoethyl phthalate.
[0046] The general formula (1) is shown below.
[0047] [Chemical formula 1]
[0048]
[0049] In the above general formula (1), R 1 , R 2 , R 3 Each independently represents a hydrogen atom, a chlorine atom, or an alkyl group having 1 to 5 carbon atoms. 1 , R 2 , R 3 A group with little steric hindrance is preferred, preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a methyl group. 1 , R 2 , R 3 They can be all the same or different.
[0050] In addition, X' represents an atomic group with a molecular weight of 472 or less and a main chain atomic number of 1 to 19. Specific examples of X' include: various alkylene groups, ether groups, ester bonds, aromatic rings, and combinations thereof. The number of atoms in the main chain of X' is more preferably greater than 1 and less than 14, and further preferably greater than 1 and less than 9. It should be noted that in this specification, the main chain of X' refers to the number of atoms of the skeleton connecting the carbonyl group and the carboxyl group in the general formula (1). In the case where X' contains a cyclic structure, there are sometimes multiple main chain atoms. In this case, the minimum value is treated as the number of atoms in the main chain of X'.
[0051] Specific examples of the compound represented by the general formula (1) include (meth)acryloyloxypropyl succinate, (meth)acryloyloxyethyl succinate, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, acryloyloxyethyl phthalate, methacryloyloxyethyl phthalate, N-carboxyethyl (meth)acrylamide, carboxyethyl thio (meth)acrylate, and carboxymethyl acrylate. In this specification, (meth)acryloyloxy represents methacryloyloxy, acryloyloxy, or both. Moreover, (meth)acrylate represents methacrylate, acrylate, or both, and (meth)acryloyl represents methacryloyl, acryloyl, or both.
[0052] The compound containing a carboxyl group is preferably a compound represented by the above general formula (1), and more preferably (meth)acryloyloxypropylsuccinic acid.
[0053] On the other hand, the amount of other structural units contained in the vinylidene fluoride copolymer, which do not contain a carboxyl group and are derived from a compound copolymerizable with the vinylidene fluoride, is 3% by mass or more and 25% by mass or less, preferably 3% by mass or more and 23% by mass or less, and more preferably 5% by mass or more and 20% by mass or less when the total amount of the structural units of the vinylidene fluoride copolymer is set to 100% by mass. If the proportion of other structural units is 3% by mass or more, the flexibility of the vinylidene fluoride copolymer is improved, and the dry adhesion of the resin-containing layer containing the resin composition is improved. On the other hand, if the amount of other structural units is excessive, it is not easy to dissolve in a solvent when it is made into a coating composition, etc. If the amount of other structural units is 25% by mass or less, the vinylidene fluoride copolymer is easily dissolved in a solvent. In addition, if the proportion of other structural units is 25% by mass or less, relatively speaking, the amount of structural units derived from vinylidene fluoride increases, and the strength of the resin-containing layer is improved. The amount of other structural units in the vinylidene fluoride copolymer can be 19 Determined by F-NMR.
[0054] Other structural units are structural units derived from compounds containing groups (such as unsaturated double bonds) that are polymerizable with vinylidene fluoride and do not contain a carboxyl group (hereinafter also referred to as "other compounds"). Examples of other compounds include fluorine-containing monomers other than vinylidene fluoride, hydrocarbon monomers such as ethylene and propylene, and the like.
[0055] Examples of fluorinated monomers include vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, fluoroalkyl vinyl ethers, and perfluoroalkyl vinyl ethers represented by perfluoromethyl vinyl ether, etc. Among these, structural units derived from chlorotrifluoroethylene or hexafluoropropylene are preferred from the viewpoint that dry adhesion and wet adhesion are easily improved.
[0056] Here, the intrinsic viscosity of the above-mentioned vinylidene fluoride copolymer is 0.5 dL / g or more and 3 dL / g or less, more preferably 0.8 dL / g or more and 2.5 dL / g or less, more preferably 1.0 dL / g or more and 2.0 dL / g or less. If the intrinsic viscosity is 0.5 dL / g or more, the stability of the coating composition described later including the resin composition is improved. On the other hand, if the intrinsic viscosity is 3 dL / g or less, the resin composition layer is easily softened by heating, and the dry adhesiveness is easily improved.
[0057] The intrinsic viscosity is a value obtained from the viscosity η1 of a solution prepared by dissolving 4 g of a vinylidene fluoride copolymer in 1 L of N,N-dimethylformamide and the viscosity η0 of N,N-dimethylformamide measured using an Ubbelohde viscometer in a thermostatic bath at 30° C. The intrinsic viscosity η is obtained by the following formula.
[0058] Intrinsic viscosity η=(1 / C)·ln(η1 / η0)
[0059] In the above formula, C is the concentration per unit of the resin composition, and is 0.4 g / dl in this case.
[0060] In addition, the melting point of the above-mentioned vinylidene fluoride copolymer is preferably 100°C or more and 165°C or less, more preferably 120°C or more and 160°C or less. If the melting point of the vinylidene fluoride copolymer is 100°C or more, the heat resistance of the obtained resin-containing layer is easy to become good. On the other hand, if the melting point of the vinylidene fluoride copolymer is 165°C or less, the polymer is easily softened by heating, and dry bonding can be performed at a relatively low temperature. The melting point of the vinylidene fluoride copolymer can be determined by heat measurement using a differential scanning calorimeter (DSC). Specifically, the vinylidene fluoride copolymer is heated from 30°C to 230°C (first heating) at 10°C / min, cooled from 230°C to 30°C (first cooling) at 10°C / min, and further heated from 30°C to 230°C (second heating) at 10°C / min, and the melting peak is determined by DSC. Then, the maximum melting peak temperature observed in the second heating is determined as the melting point of the vinylidene fluoride copolymer.
[0061] The weight average molecular weight of the above-mentioned vinylidene fluoride copolymer is preferably 50,000 to 1.2 million, more preferably 100,000 to 1 million, and further preferably 150,000 to 1 million. The above-mentioned weight average molecular weight is a polystyrene conversion value measured by gel permeation chromatography (GPC). If the weight average molecular weight of the vinylidene fluoride copolymer is within the above range, the resin composition easily satisfies the above-mentioned intrinsic viscosity.
[0062] The vinylidene fluoride copolymer having a carboxyl group is obtained by copolymerizing vinylidene fluoride, a compound containing a carboxyl group, and other compounds by a known method. Examples of methods for copolymerizing them include suspension polymerization, emulsion polymerization, solution polymerization, etc. Here, in order to adjust the melt viscosity to the above range, the amount of initiator, chain transfer agent, polymerization temperature, etc. is adjusted.
[0063] 2. Coating composition (coating liquid)
[0064] The coating composition (coating liquid) of the present invention is a composition mainly used to form a resin-containing layer for bonding the separator and electrode of a non-electrolyte secondary battery, and includes the above-mentioned resin composition. The coating composition (coating liquid) can be, for example, a composition prepared by dispersing or dissolving the above-mentioned resin composition in a solvent, and can also include an inorganic filler, etc. In addition, various additives may also be included within the scope of not impairing the purpose and effect of the present invention. Among them, the use of the coating composition (coating liquid) is not limited to forming a resin-containing layer. In this specification, the terms "coating composition" and "coating liquid" are used with the same meaning.
[0065] The amount of the above-mentioned resin composition in the coating composition can be appropriately selected according to the coating method of the coating composition, the thickness of the desired resin-containing layer, etc. Usually, with respect to the coating composition, the resin composition preferably includes more than 3 mass % and less than 50 mass % in its solid component, more preferably includes more than 5 mass % and less than 40 mass % of the resin composition, and further preferably includes more than 10 mass % and less than 30 mass % of the resin composition. If the resin composition (mainly vinylidene fluoride copolymer) of the above-mentioned scope is included in the solid component of the coating composition, then the electrode and the spacer can be firmly bonded.
[0066] The type of solvent included in the coating composition is not particularly limited as long as it can make the above-mentioned resin composition uniformly dissolve or disperse. Examples of solvents include: N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate, acetone, 2-butanone, cyclohexanone, etc. The coating composition may contain only one solvent or two or more solvents.
[0067] The amount of the solvent can be appropriately selected depending on the coating method of the coating composition, the desired thickness of the resin-containing layer, and the like.
[0068] The inorganic filler is not particularly limited as long as it has insulating properties and is resistant to heat during dry bonding or wet bonding. As described above, if the coating composition and further the resin-containing layer contain a filler, the mechanical strength of the resin composition layer can be easily maintained.
[0069] Examples of inorganic fillers include: SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, clay minerals, mica, calcium carbonate, etc. The coating composition may contain only one filler or two or more fillers. From the perspective of the safety of the secondary battery and the stability of the coating solution, the inorganic filler is preferably Al2O3, MgO, and ZnO. From the perspective of insulation and electrochemical stability, the inorganic filler is more preferably Al2O3.
[0070] Commercially available inorganic fillers may be used. For example, commercially available high-purity alumina particles such as AKP-3000, AKP-50, and AKP-20 (all manufactured by Sumitomo Chemical Co., Ltd.) may be used.
[0071] The median diameter of the inorganic filler measured by laser diffraction scattering is preferably 10 μm or less, more preferably 0.05 μm or more and 5 μm or less, and further preferably 0.10 μm or more and 2 μm or less. If the median diameter of the inorganic filler is 10 μm or less, the thickness of the resin-containing layer will not become too thick, and the secondary battery can be easily thinned.
[0072] The amount of the inorganic filler in the coating composition can be appropriately selected according to the coating method of the coating composition, the thickness of the desired resin-containing layer, etc., preferably including more than 30 mass % and less than 99 mass % in the solid component of the coating composition, more preferably more than 50 mass % and less than 95 mass %, more preferably more than 70 mass % and less than 90 mass %. If the inorganic filler of more than 30 mass % is included in the solid component of the coating composition, then when wet bonding, the OH group on the surface of the inorganic filler and the carboxyl group of the above-mentioned vinylidene fluoride copolymer are easily interacted, and the shape of the resin-containing layer is easily maintained. In addition, the mechanical strength of the laminate increases, and safety is improved.
[0073] It should be noted that the method for mixing the resin composition, the inorganic filler and the solvent is not particularly limited, and the resin composition, the inorganic filler and the solvent may be mixed by a known method.
[0074] 3. Non-aqueous electrolyte secondary battery
[0075] The secondary battery of the present invention includes: a laminate including a positive electrode, a separator, and a negative electrode; a non-aqueous electrolyte; and an outer shell covering them. In addition, a resin-containing layer containing the above-mentioned resin composition is arranged between the positive electrode and the separator of the above-mentioned laminate, and / or between the negative electrode and the separator. It should be noted that the resin-containing layer can also be arranged only between the positive electrode and the separator, and between the negative electrode and the separator, but if the resin-containing layer is arranged on both sides, the electrode and the separator are not easy to be offset, wrinkled, etc., and the strength and performance of the obtained secondary battery are improved.
[0076] It should be noted that the secondary battery may have any structure of a coin-type battery, a button-type battery, a cylindrical battery, a square battery, a laminated battery, etc. Hereinafter, each structure of the secondary battery will be described.
[0077] Electrodes (positive and negative)
[0078] The electrodes of the secondary battery can be the same as those of known secondary batteries. The electrodes generally include a current collector and a mixture layer containing an active material disposed on at least one surface of the current collector.
[0079] The material of the current collector for the negative electrode and the positive electrode is not particularly limited as long as it can extract electricity. Examples of current collectors include metal foils, metal meshes, etc. of aluminum, copper, iron, stainless steel, steel, nickel, titanium, etc. In addition, it can also be a material formed by applying the above-mentioned metal foil or metal mesh on the surface of other media. The thickness of the current collector is usually 5 μm or more and 100 μm or less.
[0080] On the other hand, the composite layer is a layer comprising an electrode active material and a binder, and a conductive aid as required. The ratio of the components constituting the composite layer can be the same as that of the composite layer of a known secondary battery. The thickness of the composite layer can be appropriately adjusted according to the type of the secondary battery, and is usually 20 μm or more and 250 μm or less.
[0081] Specific examples of the positive electrode active material contained in the positive electrode mixture layer include: LiCoO2, LiNixCo 1-x O2 (0≤x≤1) and other composite metal sulfide compounds represented by the general formula LiMY2 (M represents at least one of transition metals such as Co, Ni, Fe, Mn, Cr, V, and Y represents a sulfide element such as O, S), composite metal oxides with a spinel structure such as LiMn2O4, and olivine-type lithium compounds such as LiFePO4. It should be noted that the positive electrode active material may also be a commercially available product.
[0082] On the other hand, examples of negative electrode active materials contained in the negative electrode mixture layer include: carbon materials, metal / alloy materials, metal oxides, etc., among which carbon materials are preferred. Examples of carbon materials include: artificial graphite, natural graphite, difficult-graphitizing carbon, easy-graphitizing carbon, etc. If such carbon materials are used, the energy density of the secondary battery tends to be higher. It should be noted that the above-mentioned artificial graphite can be obtained, for example, by carbonizing an organic material, then heat-treating it at a high temperature, and crushing / classifying it. As the difficult-graphitizing carbon, for example, it can be obtained by calcining a material derived from petroleum asphalt at above 1000°C and below 1500°C. These negative electrode active materials can also be commercially available products.
[0083] The specific surface area of the positive electrode active material is preferably 0.05 m2 / g or more and 50m 2 On the other hand, the specific surface area of the negative electrode active material is preferably 0.3 m 2 / g or more and 10m 2 The specific surface area of the electrode active material can be determined by a nitrogen adsorption method.
[0084] In addition, the binder contained in the mixture layer is not particularly limited as long as it can bind the above-mentioned electrode active material and the conductive auxiliary agent described later. Examples thereof include: fluorine-containing resins such as polytetrafluoroethylene, polyvinylidene fluoride, and fluororubber; a mixture of styrene butadiene rubber and carboxymethyl cellulose; and thermoplastic resins such as polypropylene and polyethylene.
[0085] As the fluorine-containing resin, a vinylidene fluoride copolymer may be used. Examples of the vinylidene fluoride copolymer include a vinylidene fluoride-monomethyl maleate copolymer and a vinylidene fluoride copolymer obtained by copolymerizing vinylidene fluoride with the above-mentioned carboxyl group-containing compound.
[0086] The conductive additive contained in the electrode mixture layer may be any material as long as it can improve the conductivity of the electrode mixture layer. Examples of the conductive additive include carbonaceous materials such as carbon black, graphite powder, and carbon fiber; and metal powders or metal fibers such as nickel and aluminum.
[0087] There is no particular limitation on the method for forming the above-mentioned electrode. For example, a slurry containing an electrode active material, a binder, a conductive aid, and a non-aqueous solvent can be applied to the collector and dried (cured) to form the electrode. Examples of non-aqueous solvents include N-methyl-2-pyrrolidone and the like. There is no particular limitation on the coating method of the above-mentioned slurry, including a method of coating using a bar coater, a die coater, or a comma coater. In addition, the drying temperature is generally preferably above 50°C and below 150°C, and the drying time is above 1 minute and below 300 minutes. In addition, there is no particular limitation on the atmosphere during drying, and it can be under an inert gas such as nitrogen or under reduced pressure. In addition, after drying, heat treatment can be further performed as needed. In addition, instead of heat treatment or after heat treatment, pressing treatment can be further performed. In the case of pressing treatment, it is generally preferred that 1MPa(G) or more and 200MPa(G) or less. If pressing treatment is performed, the electrode density is improved.
[0088] Spacers
[0089] The separator of the secondary battery is not particularly limited as long as it can electrically insulate the positive electrode from the negative electrode and can retain the electrolyte. Examples of separators include single-layer or multi-layer porous films, non-woven fabrics, etc., and the single-layer or multi-layer porous films include: polyolefin polymers such as polyethylene and polypropylene; polyester polymers such as polyethylene terephthalate; aromatic polyamide polymers, polyimide polymers such as polyetherimide; polyether sulfone; polysulfone; polyether ketone; polystyrene; polyethylene oxide; polycarbonate; polyvinyl chloride; polyacrylonitrile; polymethyl methacrylate; ceramics, etc. In addition, it can also be glass, paper, etc.
[0090] Among these, porous membranes of polyolefin-based polymers (e.g., polyethylene, polypropylene, etc.) are preferred. Examples of commercially available polyolefin-based polymer porous membranes include Celgard (registered trademark) manufactured by Polypore (single-layer polypropylene spacers, single-layer polyethylene spacers, and polypropylene / polyethylene / polypropylene three-layer spacers, etc.), HIPORE (registered trademark) manufactured by Asahi Chemical (single-layer polyethylene), SETELA (registered trademark) manufactured by Toray Industries (single-layer polyethylene), etc. It should be noted that the spacer may be surface treated, and the layer of inorganic particles may be pre-coated.
[0091] Resin-containing layer
[0092] The resin-containing layer is a layer obtained by coating the composition containing the above-mentioned resin composition, that is, coating the above-mentioned coating composition and curing it. The resin-containing layer can be arranged between the above-mentioned positive electrode and the separator, and at least one of the negative electrode and the separator, but if it is arranged on both sides, the strength and transportability of the laminate are improved. In addition, the above-mentioned resin composition shows high adhesion to either the positive electrode and the negative electrode. Therefore, it has the advantages of being able to be used for bonding the positive electrode to the separator and bonding the negative electrode to the separator.
[0093] The thickness of the resin-containing layer is preferably 0.2 μm to 25 μm, and preferably 0.5 μm to 20 μm. The method for forming the resin-containing layer will be described in detail later.
[0094] Non-aqueous electrolyte
[0095] The non-aqueous electrolyte is a solution in which an electrolyte is dissolved in a non-aqueous solvent. Examples of the non-aqueous solvent include aprotic organic solvents that can transport cations and anions constituting the electrolyte and that do not substantially impair the function of the secondary battery.
[0096] Examples of non-aqueous solvents include organic solvents commonly used as non-aqueous electrolytes for lithium ion secondary batteries, and specific examples include carbonates, halogenated hydrocarbons, ethers, ketones, nitriles, lactones, esters, tetrahydrofuran compounds, etc. Among them, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, methyl propionate, ethyl propionate, succinonitrile, 1,3-propane sultone, fluoroethylene carbonate, vinylene carbonate, etc. are preferred. The non-aqueous electrolyte may contain only one non-aqueous solvent, or may contain two or more non-aqueous solvents.
[0097] In addition, the electrolyte is not particularly limited as long as it is a substance that can transport cations and anions through the above-mentioned non-aqueous solvent and does not substantially damage the function of the secondary battery. Examples of electrolytes in the case where the non-aqueous electrolyte secondary battery is a lithium ion secondary battery include: lithium salts of fluoride complex anions such as LiPF6, LiAsF6, LBF4; inorganic lithium salts such as LiClO4, LiCl, LiBr; and sulfonic acid lithium salts such as LiCH3SO3, LiCF3SO3, Li(CF3OSO2)2N, Li(CF3OSO2)3C, Li(CF3SO2)2N, Li(CF3SO2)3C and other organic lithium salts. The non-aqueous electrolyte may contain only one electrolyte or more than two electrolytes.
[0098] Outer shell
[0099] The shape of the secondary battery outer case is not particularly limited and can be appropriately selected according to the application of the secondary battery, etc. The outer case can be any shape as long as it can hold the laminate including the electrodes, separators, and resin-containing layers and the nonaqueous electrolyte, and can be, for example, a cylindrical can or a laminated bag.
[0100] (Method for manufacturing secondary battery)
[0101] The method for manufacturing the secondary battery is described below. Hereinafter, the case where the resin-containing layer is formed between the electrode and the separator and between the negative electrode and the separator is described as an example, but as described above, the resin-containing layer may be disposed only on one side.
[0102] The manufacturing method of the secondary battery of the present invention includes at least: a step of forming the above-mentioned resin-containing layer containing the resin composition on at least one side of at least one member selected from the group consisting of the positive electrode, the separator, and the negative electrode (resin-containing layer forming step); a step of stacking the positive electrode, the separator, and the negative electrode in a manner that the resin-containing layer is located between the positive electrode and the separator and between the negative electrode and the separator to form a stack (stacking step); and a step of hot pressing the stack (hot pressing step). Before or after the hot pressing step, it may also include: a step of filling the above-mentioned stack into the outer shell and impregnating the stack with a non-aqueous electrolyte (non-aqueous electrolyte impregnation step).
[0103] ·Resin-containing layer forming process
[0104] In the resin-containing layer forming step, the resin-containing layer containing the resin composition is formed on at least one side of at least one member selected from the group consisting of the positive electrode, the separator, and the negative electrode. The method for forming the resin-containing layer can be any method as long as the coating composition is applied and cured, and any of the following methods can be used.
[0105] (1) A coating composition is applied to one side of an electrode (positive electrode, negative electrode) and cured to form a laminate of the electrode and a resin-containing layer (also referred to as a "laminated electrode" in this specification).
[0106] (2) A coating composition is applied to one or both surfaces of a separator and cured to form a laminate of a separator and a resin-containing layer (also referred to as a "lamination separator" in this specification).
[0107] (3) The coating composition is applied to a separately prepared substrate, cured, and then the coating film is peeled off the substrate and bonded to a separator or an electrode. Examples of the substrate include substrates made of polyethylene terephthalate (PET).
[0108] Among the above methods, (1) the method of forming a stacking electrode and (2) the method of forming a stacking spacer are preferred in terms of simplifying the substrate peeling process and the stacking process. In addition, the method of forming a stacking spacer (2) is particularly preferred because it can form a resin-containing layer without affecting the electrode.
[0109] The coating method of the coating composition is not particularly limited. For example, the coating method may be a method using the following devices: a bar coater; a die coater; a comma coater; a gravure coater such as a direct gravure coater, a reverse gravure coater, a contact gravure coater, an offset gravure coater, etc.; a reverse roll coater; a micro gravure coater; an air knife coater; a dip coater, etc.
[0110] In addition, the curing method of the above-mentioned coating composition can include immersion or drying in a non-solvent. They can be combined. As a non-solvent, a solvent such as water that does not dissolve the resin composition can be used. In addition, in addition to the non-solvent, a poor solvent such as ethanol can also be included. The drying temperature in the case of drying is usually above 40°C and below 190°C, more preferably above 50°C and below 180°C. The drying time is preferably above 1 second and below 15 hours. In addition, the atmosphere during drying is not particularly limited, and it can be dried under an inert gas atmosphere such as nitrogen or under reduced pressure. In addition, after drying, it can also be further heat-treated as needed.
[0111] Lamination process
[0112] In the stacking process, the components are arranged in the order of the positive electrode, the resin-containing layer, the separator, the resin-containing layer, and the negative electrode. The stacking method of the stacking process can be appropriately selected according to the method by which the above-mentioned resin-containing layer is produced. For example, in the resin-containing layer forming process, when a stacking electrode having a resin-containing layer stacked on one side of the electrode is prepared, the stacking electrode and the separator are stacked in such a manner that the resin-containing layer of the stacking electrode is opposite to the diaphragm. In addition, in the above-mentioned resin-containing layer forming process, when a stacking separator having a resin-containing layer formed on both sides of the separator is prepared, the stacking separator is clamped between the positive electrode and the negative electrode.
[0113] It should be noted that the laminate formed in the lamination process may include only one unit consisting of a positive electrode, a resin-containing layer, a separator, a resin-containing layer, and a negative electrode, or may include a plurality of such units. When a plurality of units are laminated, a resin-containing layer and a separator may also be disposed between the units.
[0114] Hot pressing process
[0115] The hot pressing process is a process for hot pressing the laminate produced in the above-mentioned lamination process. In the present invention, if dry bonding is performed before the above-mentioned laminate is impregnated with a non-aqueous electrolyte, the resin-containing layer is firmly adhered to the separator and the electrode. Therefore, in the hot pressing process, it is preferred to at least perform dry bonding, and wet bonding can also be performed after the above-mentioned laminate is impregnated with a non-aqueous electrolyte. It should be noted that in the manufacturing method of the secondary battery of the present invention, high adhesion can be obtained for both the positive electrode and the negative electrode by dry bonding. In addition, by performing wet bonding on the laminate, the adhesion between the layers is further improved.
[0116] (1) Dry bonding
[0117] Dry bonding is performed before impregnating the above-mentioned laminate with a nonaqueous electrolyte. As far as the temperature during dry bonding is concerned, considering the heat resistance of the electrode and the separator, the lowest temperature at which a significant change (including simple state changes such as chemical structure changes based on decomposition, melting / gasification, etc.) is observed in any of the electrodes and separators is appropriately selected as the upper limit. For example, the heating temperature is preferably above 40°C and below 220°C, more preferably above 50°C and 120°C. In addition, the heating time is preferably above 1 second and below 15 hours. In addition, with respect to the pressure during pressing, the lowest pressure at which a significant structural change (density change of the electrode, fracture, change in the air permeability of the separator, etc.) is observed in any of the electrodes and separators is appropriately selected as the upper limit. For example, the pressure during pressing is preferably above 0.01MPa(G) and 30MPa(G), more preferably above 0.5MPa(G) and below 20MPa(G).
[0118] (2) Wet bonding
[0119] Wet bonding is performed after the above-mentioned non-aqueous electrolyte is impregnated into the laminate. As for the temperature during wet bonding, considering the heat resistance of the electrode, the separator and the electrolyte, the lowest temperature at which a significant change (including simple state changes such as chemical structure changes based on decomposition, melting / gasification, etc.) is observed in any one of the electrode, the separator and the non-aqueous electrolyte is appropriately selected as the upper limit. For example, the temperature during hot pressing is preferably above room temperature and below 130°C, more preferably above 40°C and below 100°C. The pressure during hot pressing is preferably above 0.01MPa(G) and 10MPa(G), more preferably above 0.1MPa(G) and below 8MPa(G). Moreover, before hot pressing, the laminate and the non-aqueous electrolyte may also be preheated. The preheating time is preferably above 1 second and below 1 hour. In addition, the pressing time under the above-mentioned pressure is more preferably above 1 second and below 1 hour.
[0120] Non-aqueous electrolyte impregnation process
[0121] As described above, the present invention may further include a step of filling the dry-bonded laminate or the laminate not dry-bonded into the outer shell and impregnating the outer shell with a non-aqueous electrolyte. The method of filling the laminate and the method of impregnating the outer shell with a non-aqueous electrolyte are the same as the known method of filling the laminate and the method of impregnating the outer shell with a non-aqueous electrolyte of a secondary battery.
[0122] Example
[0123] Hereinafter, the present invention will be described in more detail with reference to Examples, but the scope of the present invention is not limited to and interpreted by these Examples.
[0124] 1. Preparation of resin composition
[0125] Each resin composition (vinylidene fluoride copolymer) was prepared in the following procedure.
[0126] (1) Example A1 (Preparation of Vinylidene Fluoride Copolymer 1)
[0127] 286 parts by mass of ion exchange water, 0.1 parts by mass of methylcellulose, 82 parts by mass of vinylidene fluoride (VDF), 18 parts by mass of hexafluoropropylene (HFP), 0.5 parts by mass of acryloxypropyl succinate (APS), and 1.5 parts by mass of diisopropyl peroxydicarbonate were added to a 2L autoclave, and polymerization was carried out at 28°C. The obtained copolymer was heat-treated at 95°C for 60 minutes, dehydrated, washed with water, and then dried at 80°C for 20 hours to obtain VDF-HFP-APS. The copolymer particles contained 15.3% by mass of HFP, 0.3% by mass of APS, and η was 1.7 dL / g. The copolymer was referred to as copolymer 1.
[0128] (2) Example A2 (Preparation of Vinylidene Fluoride Copolymer 2)
[0129] VDF-HFP-APS was polymerized in the same manner as in Copolymer 1 to obtain Copolymer 2. Copolymer 2 contained 6.0 mass % of HFP and 0.8 mass % of APS, and η was 1.5 dL / g.
[0130] (3) Example A3 (Preparation of Vinylidene Fluoride Copolymer 3)
[0131] VDF-HFP-APS was polymerized in the same manner as in Copolymer 1 to obtain Copolymer 3. Copolymer 3 contained 9.1% by mass of HFP and 0.9% by mass of APS, and η was 1.5 dL / g.
[0132] (4) Comparative Example A1 (Preparation of Vinylidene Fluoride Copolymer 4)
[0133] Except that HFP was not added, VDF-APS was polymerized in the same manner as in Copolymer 1 to obtain Copolymer 4. Copolymer 4 contained 0.7 mass % of APS and η was 2.5 dL / g.
[0134] (5) Comparative Example A2 (Preparation of Vinylidene Fluoride Copolymer 5)
[0135] VDF-HFP-APS was polymerized in the same manner as in Copolymer 1 to obtain Copolymer 5. Copolymer 5 contained 7.8% by mass of HFP and 0.3% by mass of APS, and η was 3.3 dL / g.
[0136] (6) Comparative Example A3 (Preparation of Vinylidene Fluoride Copolymer 6)
[0137] VDF-HFP-APS was polymerized in the same manner as in Copolymer 1 to obtain Copolymer 6. Copolymer 6 contained 26.0 mass % of HFP and 0.4 mass % of APS, and η was 1.9 dL / g.
[0138] (7) Comparative Example A4 (Preparation of Vinylidene Fluoride Copolymer 7)
[0139] VDF-HFP was polymerized in the same manner as in Copolymer 1 except that APS was not added, thereby obtaining Copolymer 7. Copolymer 7 contained 13.5% by mass of HFP, and η was 1.4 dL / g.
[0140] (8) Comparative Example A5 (Preparation of Vinylidene Fluoride Copolymer 8)
[0141] VDF-HFP-APS was polymerized in the same manner as in Copolymer 1 to obtain Copolymer 8. Copolymer 8 contained 5.6% by mass of HFP and 1.5% by mass of APS, and η was 1.5 dL / g. 2. Analysis of the resin composition (vinylidene fluoride copolymer)
[0142] The structural unit amounts of the vinylidene fluoride copolymers prepared in Examples A1 to A3 and Comparative Examples A1 to A5 were determined by the following method, and the intrinsic viscosities of the vinylidene fluoride copolymers were measured by the following method. The results are shown in Table 1.
[0143] (1) Determination of the structural unit content of vinylidene fluoride copolymers
[0144] pass 1 H-NMR and 19 The amount of the structural units constituting the vinylidene fluoride copolymer was determined by F-NMR.
[0145] (2) Determination of intrinsic viscosity η
[0146] A solution containing a resin composition was prepared by dissolving 4 g of the vinylidene fluoride copolymer prepared in Examples A1 to A3 and Comparative Examples A1 to A5 in 1 L of N,N-dimethylformamide. Then, the viscosity η1 of the solution containing the resin composition was measured in a constant temperature bath at 30°C using an Ubbelohde viscometer. Similarly, the viscosity η0 of N,N-dimethylformamide was measured in a constant temperature bath at 30°C using an Ubbelohde viscometer. Then, the intrinsic viscosity η was calculated based on the following formula.
[0147] Intrinsic viscosity η=(1 / C)·ln(η1 / η0)
[0148] In the above formula, C is the concentration per unit of the resin composition, and is 0.4 g / dl in this case.
[0149] [Table 1]
[0150]
[0151] 3. Preparation of coating composition and fabrication of secondary battery
[0152] (1) Examples B1 to B3 and Comparative Examples B1 to B5
[0153] Preparation of coating composition
[0154] The resin composition was dispersed in N-methyl-2-pyrrolidone (NMP) at room temperature so that the concentration of the resin composition was 5% by mass, and then the solution temperature was raised to 50° C. to dissolve the resin composition (hereinafter referred to as a polymer solution). 400 parts by mass of the polymer solution (resin composition: 20 parts by mass) and 80 parts by mass of alumina particles (AKP-20, manufactured by Sumitomo Chemical Co., Ltd., average particle size 0.46 μm) were mixed, and NMP was added to obtain a coating composition having a solid content of 15% by mass.
[0155] 4. Evaluation of the resin-containing layer
[0156] (1) Preparation of positive electrode
[0157] NMP was added to 94 parts by mass of LiNiCoMnO2 (MX6, manufactured by Umicore), 3 parts by mass of a conductive aid (SuperP TIMCAL), and 3 parts by mass of PVDF (polyvinylidene fluoride, (KF#7200, manufactured by KUREHA)) to make a slurry, which was then applied to an Al foil (thickness 15 μm). After drying, the slurry was pressed and heat treated at 120°C for 3 hours to obtain an electrode with a volume density of 3.0 g / cm 3 , weight per unit area is 103g / m 2 The positive electrode.
[0158] (2) Preparation of negative electrode
[0159] Water was added to 95 parts by mass of BTR918 (modified natural graphite, manufactured by BTR), 2 parts by mass of a conductive aid (manufactured by SuperP TIMCAL), 2 parts by mass of SBR (styrene butadiene rubber) latex (BM-400 manufactured by ZEON Japan), and 1 part by mass of CMC (carboxymethyl cellulose, CELLOGEN 4H manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) to make a slurry, which was then applied to a Cu foil (thickness 10 μm). After drying, the slurry was pressed, and after heat treatment at 150°C for 3 hours, the electrode volume density was obtained to be 1.6 g / cm 3 , weight per unit area is 60g / m 2 of the negative electrode.
[0160] (3) Preparation of spacers for lamination
[0161] The coating composition was applied to one side of a spacer (single-layer polyethylene, thickness 20 μm) using a wire rod with a wet coating amount of 24 μm. Then, it was immersed in a coagulation bath (water) for 3 minutes. After that, it was immersed in a cleaning liquid (water) for 1 minute and dried at 70°C under nitrogen for 30 minutes. Furthermore, a heat treatment was performed in a vacuum at 70°C for 2 hours.
[0162] (4) Wet Adhesion of Resin-Containing Layer
[0163] The positive electrode obtained above is cut into 2.5×5.0cm, and the stacking separator is cut into 3.0×6.0cm, and the positive electrode mixture layer of the positive electrode and the resin-containing layer of the stacking separator are joined in a manner that they face each other. The joint is placed in an aluminum laminate bag, and after injecting 160μL of electrolyte (EC (ethylene carbonate) / EMC (ethyl methyl carbonate) = 3 / 7 (volume ratio), 1.2M LiPF6 and VC (vinylene carbonate) mixture (VC concentration: 1 mass%)), it is vacuum sealed and left to stand at 25°C overnight. A flat press is used to perform hot pressing from the outside of the aluminum laminate bag to bond the stacking separator to the positive electrode, and a sample for peel strength measurement (stacking separator / positive electrode) is obtained. The sample for peel strength measurement is made by hot pressing for 2 minutes at a surface pressure of about 4MPa (G) after residual heat for 1 minute at an arbitrary temperature. The positive electrode collector side of the prepared sample for peel strength measurement was fixed to a support, and the support was fixed to a tensile testing machine ("STA-1150 UNIVERSALTESTING MACHINE" manufactured by ORIENTEC). The spacer was stretched at a head speed of 200 mm / min, and a 180° peel test was performed to measure the peel strength between the resin-containing layer and the positive electrode.
[0164] (5) Dry Adhesion of Resin-Containing Layer
[0165] The positive electrode or negative electrode obtained above was cut into 2.5×5.0 cm. On the other hand, the lamination separator was cut into 3.0×6.0 cm. Then, the positive electrode mixture layer of the positive electrode or the negative electrode mixture layer of the negative electrode and the resin-containing layer of the lamination separator were joined so that they faced each other.
[0166] The bonded body was hot pressed using a roll press to bond the resin-containing layer of the lamination separator to the positive electrode or negative electrode to obtain a sample for measuring peel strength. The sample for measuring peel strength was prepared by hot pressing at 70°C, 2 rpm, and a linear pressure of about 4 N / mm.
[0167] The collector side of the positive electrode or negative electrode of the prepared sample for peel strength measurement is fixed to a support, and the support is fixed to a tensile testing machine ("STA-1150 UNIVERSAL TESTING MACHINE" manufactured by ORIENTEC), and the spacer is stretched at a head speed of 200 mm / min to perform a 180° peel test, and the peel strength between the positive electrode and the resin-containing layer and the peel strength between the negative electrode and the resin-containing layer are measured respectively.
[0168] [Table 2]
[0169]
[0170] As shown in Table 2, in the lamination separators prepared using the resin compositions of Examples A1 to A3, good results were obtained in terms of dry adhesion of both the positive electrode and the negative electrode. In the resin compositions of Examples A1 to A3, the amount of structural units derived from vinylidene fluoride was 73.7% by mass or more and 96.9% by mass or less, the amount of structural units having carboxyl groups was 0.1% by mass or more and 1.5% by mass or less, and the amount of other structural units was 3% by mass or more and 30% by mass or less, and the intrinsic viscosity of the solution obtained by dissolving 4g of the vinylidene fluoride copolymer in 1L of N,N-dimethylformamide at 30°C was 0.5dL / g or more and 3dL / g or less. In addition, wet adhesion was also sufficiently ensured at this time (Examples B1 to B3).
[0171] On the other hand, the resin-containing layer of the stacked spacer has low dry adhesion to either electrode when the vinylidene fluoride copolymer does not contain a carboxyl-containing structural unit (Comparative Example B4). It can be considered that when the laminate is heated and softened to make it close, the resin-containing layer cannot chemically interact with the OH group on the surface of the electrode or the spacer, so it is not easy to obtain high adhesion. On the other hand, in the case where the vinylidene fluoride copolymer does not contain other structural units, the dry adhesion is also low (Comparative Example B1). It can be considered that the softness of the vinylidene fluoride copolymer is low, and the vinylidene fluoride copolymer is not easy to fit with the electrode and the spacer. In addition, in the case where the inherent viscosity of the vinylidene fluoride copolymer is too high, the dry adhesion is also low (Comparative Example B2). It can be considered that even if the resin composition with high inherent viscosity is softened by hot pressing, the mobility of the resin composition is also low, and the vinylidene fluoride copolymer is not easy to penetrate into the electrode and the spacer, so the bonding strength is not easy to improve. Moreover, in the case where the amount of other structural units is too much, the adhesion of the negative electrode tends to become lower (Comparative Example B3). On the other hand, when the amount of the carboxyl group-containing structural unit is too large, it is impossible to achieve both good wet adhesiveness and good dry adhesiveness (Comparative Example B5).
[0172] This application claims priority based on Japanese Patent Application No. 2020-144555 filed on August 28, 2020. The contents described in the specification of that application are incorporated herein by reference in their entirety.
[0173] Industrial Applicability
[0174] The resin composition of the present invention is excellent in dry adhesion to both positive and negative electrodes and is therefore very useful in the production of electrodes for secondary batteries.
Claims
1. A coating agent, comprising the following vinylidene fluoride copolymer, wherein the vinylidene fluoride copolymer has: 73.7% by mass or more and 96.9% by mass or less of structural units derived from vinylidene fluoride, 0.3% by mass or more and 1.0% by mass or less of a structural unit derived from a compound represented by the following general formula (1), and 3% by mass or more and 25% by mass or less of other structural units that do not contain a carboxyl group and are derived from a compound that is copolymerizable with the vinylidene fluoride, in, The total amount of the structural units constituting the vinylidene fluoride copolymer is 100 mass %, The intrinsic viscosity of a solution prepared by dissolving 4 g of the vinylidene fluoride copolymer in 1 L of N,N-dimethylformamide at 30° C. is 1.0 dL / g or more and 3.0 dL / g or less. [Chemical formula 1] R in the general formula (1) 1 , R 2 , R 3 Each independently represents a hydrogen atom, a chlorine atom, or an alkyl group having 1 to 5 carbon atoms, and X' represents an atomic group having 1 to 19 atoms in the main chain and a molecular weight of 472 or less.
2. The coating agent according to claim 1, in, The other structural units are structural units derived from chlorotrifluoroethylene or hexafluoropropylene.
3. A coating composition, comprising: A solvent and a coating agent according to claim 1 or 2.
4. The coating composition according to claim 3, in, The solid content contains 30% by mass or more and 99% by mass or less of an inorganic filler having a median diameter of 10 μm or less as measured by a laser diffraction scattering method.
5. A stacking electrode, comprising: electrodes; and The resin-containing layer is disposed on at least one side of the electrode and comprises the coating agent according to claim 1 or 2.
6. A lamination spacer, comprising: spacers; and The resin-containing layer is disposed on at least one surface of the separator and contains the coating agent according to claim 1 or 2.
7. A non-aqueous electrolyte secondary battery, comprising a positive electrode, a separator and a negative electrode, A resin-containing layer containing the coating agent according to claim 1 or 2 is further provided between the positive electrode and the separator and / or between the negative electrode and the separator.
8. A method for manufacturing a non-aqueous electrolyte secondary battery, the manufacturing method include: A step of applying the coating composition according to claim 3 or 4 to at least one surface of at least one member selected from the group consisting of a positive electrode, a separator, and a negative electrode, and curing the composition to form a resin-containing layer; A step of stacking the positive electrode, the separator, and the negative electrode to form a stacked body in such a manner that the resin-containing layer is located between the positive electrode and the separator and / or between the negative electrode and the separator; and A step of heat-pressing the laminate.
Citation Information
Patent Citations
Vinylidene fluoride copolymer, method for producing the same, gel electrolyte and nonaqueous battery
JP2015172101A
Secondary battery separator and lithium secondary battery including the same
JP2017117788A
Control system of equipment
JP2020144555A
Method for producing resin film for non-aqueous electrolyte secondary battery and resin film for non-aqueous electrolyte secondary battery
WO2014002937A1
Vinylidene fluoride copolymer, method for producing same, gel electrolyte and nonaqueous battery
CN106103508A
